189k views
19 votes
Show that (4p^2-3q)^2+48p^2q =(4p^2+3q^2)​

User Seggy
by
5.3k points

1 Answer

8 votes

Given:

The statement is


(4p^2-3q)^2+48p^2q=(4p^2+3q^2)

To prove:

The given statement.

Solution:

We have,


(4p^2-3q)^2+48p^2q=(4p^2+3q^2)

Now,


LHS=(4p^2-3q)^2+48p^2q

Using
(a-b)^2=a^2+b^2-2ab, we get


LHS=(4p^2)^2+(3q)^2-2(4p^2)(3q)+48p^2q


LHS=(4p^2)^2+(3q)^2-24p^2q+48p^2q


LHS=(4p^2)^2+(3q)^2+24p^2q

It can be rewritten as


LHS=(4p^2)^2+(3q)^2+2(4p^2)(3q)

Using
(a+b)^2=a^2+b^2+2ab, we get


LHS=(4p^2+3q^2)


LHS=RHS

Hence proved.

User Johnathan Au
by
6.0k points